Ophthalmic complications in patients with nonvalvular atrial fibrillation and type 2 diabetes prescribed rivaroxaban or warfarin. (24th May 2021) - Costa, O; Ho, K; Caranfa, JT; Vardar, B; Abdelgawwad, K; Brescia, CW; Coleman, CI
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Bayer AG Berlin, Germany INTRODUCTION: Patients with type 2 diabetes (T2D) are at an increased risk of ophthalmic complications compared to those without. Ophthalmic complications in T2D patients with comorbid nonvalvular atrial fibrillation (NVAF) may include ophthalmic bleeding and/or diabetic retinopathy. PURPOSE: We sought to evaluate ophthalmic complications in patients with NVAF and T2D prescribed rivaroxaban or warfarin for stroke prevention. METHODS: Optum® de-identified electronic health record (EHR) data from 11/2010-3/2020 were utilized. Adults with NVAF and T2D, newly started on rivaroxaban or warfarin and with ≥12 months of prior EHR activity were included. Patients were excluded if they received any oral anticoagulation in the prior 12 months, had valvular disease or pre-existing diabetic retinopathy. Our primary outcome was the incidence rate of any ophthalmic complication including non-traumatic bleeding (choroidal, intraocular, retinal, vitreous) or diabetic retinopathy.  Ophthalmic bleeds typically associated with trauma (hyphema, orbital) were excluded from our outcomes.  Hazard ratios (HR) with 95% confidence intervals (CIs) were calculated using propensity score-overlap weighted Cox regression. RESULTS: We included 26, 537 rivaroxaban and 61, 690 warfarin patients. The average age of patients was 69 ± 9 years, CHA2DS2VASc score was 4.1 ± 1.5 and HASBLED 1.5 ± 0.9. Thirty-two percent of patients had an a1c ≥7.0 and 16% an a1c≥8.0. Rivaroxaban was associated with a 15% (95%CI = 8-21%) relative hazard reduction of any ophthalmic complication (incidence rate = 1.25 vs. 1.46%/year) (Table), driven by reductions in both ophthalmic bleeding (HR = 0.80) and diabetic retinopathy (HR = 0.85). CONCLUSIONS: Rivaroxaban was associated with a reduction in ophthalmic complications compared to warfarin.